Measurement of branching fractions and resonance contributions for B0 --> D0K+pi- and search for B0 --> D0K+pi- decays. - Aubert, B; Barate, R; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges, E; Palano, A; Pappagallo, M; et al. (2006)
Using 226 x 10(6) gamma(4S) --> BB events collected with the BABAR detector at the PEP-II e+e- storage ring at the Stanford Linear Accelerator Center, we measure the branching fraction for B0 --> D0K+pi-, excluding B0 --> D*-K+, to be beta(B0 --> D0K+pi-) = (88 +/- 15 +/- 9) x 10(-6). We observe B0 --> D0K*(892)0 and B0 --> D2*(2460)-K+ contributions. The ratio of branching fractions beta(B0 --> D*-K+)/beta(B0 --> D*-pi+) = (7.76 +/- 0.34+/-0.29)% is measured separately. The branching fraction for the suppressed mode B0 --> D0K+pi- is beta(B0 --> D0K+pi-) < 19 x 10(-6) at the 90% confidence level.